2009
DOI: 10.2106/jbjs.g.01371
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Early Wound Complications Following Primary Total Knee Arthroplasty

Abstract: Patients requiring early surgical treatment for wound-healing problems after primary total knee arthroplasty are at significantly increased risk for further complications, including deep infection and/or major subsequent surgery, specifically, resection arthroplasty, amputation, or muscle flap coverage. These results emphasize the importance of obtaining primary wound-healing after total knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
155
0
18

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(174 citation statements)
references
References 33 publications
1
155
0
18
Order By: Relevance
“…Success of two-stage exchange arthroplasty for periprosthetic infection has been reported to be between 66% and 91% in several large series [9,21,22,30]. Our study supports some previous studies [7,22,23] that showed that patients should be counseled that the results of two-stage exchange arthroplasty for infection are worse in the presence of superimposed soft tissue compromise warranting flap reconstruction. It would be beneficial for future studies to prospectively compare alternative modalities for soft tissue coverage for similar defects in similar hosts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Success of two-stage exchange arthroplasty for periprosthetic infection has been reported to be between 66% and 91% in several large series [9,21,22,30]. Our study supports some previous studies [7,22,23] that showed that patients should be counseled that the results of two-stage exchange arthroplasty for infection are worse in the presence of superimposed soft tissue compromise warranting flap reconstruction. It would be beneficial for future studies to prospectively compare alternative modalities for soft tissue coverage for similar defects in similar hosts.…”
Section: Discussionsupporting
confidence: 88%
“…Galat et al [7] found that 0.33% of patients undergoing TKA will have wound complications requiring surgical treatment, but those who did were five times more likely to undergo major operative intervention compared with patients without wound complications. In particular, postoperative wounds that progress to substantial skin necrosis and exposure of the underlying hardware greatly increase the risk of having a deep periprosthetic infection develop, potentially initiating a catastrophic cascade leading to loss of the prosthesis and arthrodesis or amputation of the limb [5,16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the time the tissue is exposed to the outside environment is prolonged in the MIS group, which may lead to potential wound contamination and perioperative hypoxia. The knee is a superficial joint, being easy to expose surgically, and yet superficial wound-healing problems after primary TKA are at increased risk for additional complications, including deep infection and/or major subsequent surgery, specifically, resection arthroplasty, amputation, or muscle flap coverage [13]. The much higher infection rates and wound problems in the MIS group should not be ignored.…”
Section: Total (95% Ci)mentioning
confidence: 99%
“…In particular, restoration of soft-tissue defects of both skin and underlying capsule/muscle is critical to the elimination of infection and ultimate attainment of a functional knee. The incidence of wound problems requiring return to the OR within 30 days of the index TKA is 0.33% [1]. Gastrocnemius rotational flaps can provide coverage for major wound defects both simply and effectively [2], but some research suggests that comorbidities like diabetes and peripheral vascular disease can increase the risk these flaps may fail [2].…”
mentioning
confidence: 99%